Colonisation of the alpine tundra by trees: alpine neighbours assist late-seral but not early-seral conifer seedlings. (3rd July 2020) - Jabis, Meredith D.; Germino, Matthew J.; Kueppers, Lara M.
ABSTRACT: Background : Climate change is projected to alter the elevation and latitude of treeline globally. Seed germination and seedling survival are critical controls on treeline expansion. Neighbouring alpine plants, either through competition for resources or through altered microclimate, also affect seedlings emerging in the alpine zone. With warming, alpine plant species may interact with each other more or less strongly. Aims : To determine whether establishing tree seedlings and an alpine herb are similarly sensitive to alpine plant neighbours under ambient and altered climate. Methods : We imposed active heating, watering, and removed all plants adjacent to emerging conifer seedlings and an alpine herb. Results : Picea engelmannii seedlings showed lower survival compared with Pinus flexilis 3 weeks following neighbour removal, and after 1 year only survived in watered plots. Pinus seedlings responded to neighbour removal by lowering the quantum yield of photosynthesis (ϕPSII ). Contrary to expectations from the stress gradient hypothesis, survival was reduced without neighbours near the low-elevation range limit of Chionophila jamesii . Conclusions : Pinus flexilis has higher expansion potential into the alpine, while Picea engelmannii requires moist conditions that could be facilitated by neighbours to expand its range. This implies likely range expansion by P. flexilis with consequences for alpine plant diversity and ecosystem function.